2021
DOI: 10.1371/journal.pone.0250881
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of underachieved and overachieved fertility among women with completed fertility in Ghana

Abstract: Background A woman’s ability to achieve her preferred family size is critical in addressing issues of high fertility in sub-Saharan Africa. The socio-cultural context in sub-Saharan Africa presents some difficulty for the attainment of preferred fertility for many women. Few studies in sub-Saharan Africa have examined the extent to which women are unable to achieve their preferred family sizes. This study, therefore, examines the factors that are associated with the non-attainment of women’s preferred fertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…At a younger age, men may be using contraceptives with the intention of spacing out childbirth and not necessarily for limiting childbirth. This finding is similar to those of the study carried out by Yeboah et al (2021b) who explained that modern contraceptives used by women were used to space out high parity rather than with the intention of limiting child births. However, at older ages, men might use contraceptive methods to prevent having additional children.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…At a younger age, men may be using contraceptives with the intention of spacing out childbirth and not necessarily for limiting childbirth. This finding is similar to those of the study carried out by Yeboah et al (2021b) who explained that modern contraceptives used by women were used to space out high parity rather than with the intention of limiting child births. However, at older ages, men might use contraceptive methods to prevent having additional children.…”
Section: Discussionsupporting
confidence: 89%
“…Extant studies on fertility desires have focused mainly on women (Ahinkorah et al 2021b;Kebede et al 2021;Keesara et al 2018;Yeboah et al 2021b) and persons living with HIV (Kimani et al 2015), with few studies having been conducted on men (Akinyemi and Odimegwu 2021;Wawire et al 2013). Sarnak and Becker (2022) examined the accuracy of wives' proxy reports of husbands' fertility preferences in SSA and found that wives across a number of countries either inaccurately perceive or are uncertain of their husband's fertility preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of education was also significantly associated with CEB, and those who had obtained higher education had lower CEB, lower odds of one or more births and lower odds of high births. This could be attributed to the fact that those with higher education spend more time in training or knowledge acquisition 44 47. Their investment in education indirectly allocates the early years of their life development to set other priorities and postpone childbearing after securing an established profession.…”
Section: Discussionmentioning
confidence: 99%
“…Nibaruta et al (2021) provided evidence from Burundi that the absence of infant mortality risk in the household is associated with a low fertility rate. In Ghana, some authors have demonstrated that women who have experienced the death of a child have greater fertility (Yeboah et al, 2021;Angko et al, 2022). In contrast to these authors, Mohamud (2023) found that the infant mortality rate in Somalia has a positive effect on the fertility of women in the long run.…”
Section: Child Mortalitymentioning
confidence: 96%